Environmental adaptation and reproductive mechanisms of Codium fragile subsp. fragile in the Bohai Bay - Jingjing Zi; Zhiying Wang; Lanping Ding (Ecotoxicology and Environmental Safety)
Bohai Bay, a typical semi-enclosed bay with limited water exchange capacity, has seen increasing demand for large-scale seaweed cultivation as a sustainable resource. Codium fragile subsp. fragile (Suringar) Hariot has established stable populations in artificial diversion channels within Bohai Bay, demonstrating strong environmental adaptability and commercial cultivation potential. This study systematically evaluates the effects of temperature, salinity, and light intensity on the growth, antioxidant activity, and photosynthetic performance of Codium fragile subsp. fragile under controlled conditions. The results identified the optimal growth conditions as 20°C, salinity of 30, and light intensity of 3000 Lux. Additionally, the highest gamete release rate was observed at 25°C, salinity of 20, and light intensity of 1000 Lux, while optimal conditions for sporeling growth were 20°C, salinity of 30, and 1000 Lux. Transcriptomic analysis revealed significant temperature-dependent effects (20°C and 25°C) on both growth and reproduction, with 2668 differentially expressed genes (DEGs), of which 1663 were upregulated. At 20°C, genes associated with photosynthesis, carbon metabolism, and nucleic acid synthesis were upregulated, promoting growth and reproductive development. In contrast, at 25°C, the upregulation of heat shock proteins and antioxidant enzymes indicated enhanced stress tolerance. By integrating physiological and transcriptomic data, this study provides new insights into the environmental adaptation strategies of Codium fragile subsp. fragile, supporting its artificial cultivation and commercial applications.